The Study of the Effectiveness of Hallucinogen Educational Multimedia on Attitude and Knowledge of High School Students - Smmayeh Fadaei; Esmaeel Zaraii (Drug Control Headquarters, Research and Education Office, 2010)
Objective: The main purpose of the present study was to research the effectiveness of hallucinogen educational multimedia on attitude and knowledge of high school students. Method: The research design was semi experimental namely: pre test and post test single group. Population was included of all first grade high school students of 19th region of Tehran city. The sample was 30 first grade high school students of Shahid Kalhor high school, which is placed in 19th region of Tehran city. The sample selected by purposeful sampling. After producing of hallucinogen educational software in multimedia method and research questionnaires, first attitude and knowledge questionnaires were administered among selected sample. After that, hallucination educational multimedia was done among selected sample and post test administered again by attitude and knowledge questionnaires. Results: The results indicated that hallucinogen educational multimedia was affected on first grade high school students' attitude and knowledge, and training has important role on improving of students' attitude and knowledge toward hallucination substances. Conclusion: This method can be useful in prevention of addiction.